2013
DOI: 10.1371/journal.pone.0071569
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Turn-Taking in a Two-Person Conversation on the Gaze of a Viewer

Abstract: In natural conversation, the minimal gaps and overlaps of the turns at talk indicate an accurate regulation of the timings of the turn-taking system. Here we studied how the turn-taking affects the gaze of a non-involved viewer of a two-person conversation. The subjects were presented with a video of a conversation while their eye gaze was tracked with an infrared camera. As a control, the video was presented without sound and the sound with still image of the speakers. Turns at talk directed the gaze behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 21 publications
8
55
0
Order By: Relevance
“…In both experiments, anticipatory looking was primarily driven by question transitions, a pattern that has not been previously reported in other anticipatory gaze studies, on children or adults (Hirvenkari et al, 2013;Keitel et al, 2013;Tice (Casillas) and Henetz, 2011). Questions make an upcoming speaker switch immediately relevant, helping the listener to predict with high certainty what will happen next (i.e., an answer from the addressee), and are often easily identifiable by overt prosodic and lexicosyntactic cues.…”
Section: The Question Effectsupporting
confidence: 73%
See 3 more Smart Citations
“…In both experiments, anticipatory looking was primarily driven by question transitions, a pattern that has not been previously reported in other anticipatory gaze studies, on children or adults (Hirvenkari et al, 2013;Keitel et al, 2013;Tice (Casillas) and Henetz, 2011). Questions make an upcoming speaker switch immediately relevant, helping the listener to predict with high certainty what will happen next (i.e., an answer from the addressee), and are often easily identifiable by overt prosodic and lexicosyntactic cues.…”
Section: The Question Effectsupporting
confidence: 73%
“…Prior work using similar experimental procedures has found that adults and children make anticipatory gaze shifts to upcoming talkers within a wide time frame; the earliest shifts occur before the end of the prior turn, and the latest occur after the onset of the response turn, with most shifts occurring in the interturn gap (Hirvenkari et al, 2013;Keitel et al, 2013;Tice (Casillas) and Henetz, 2011). Following prior work, we measured how often our participants shifted their gaze from the prior to the upcoming speaker before the shift in gaze could have been initiated in reaction to the onset of the speaker's response.…”
Section: Data Preparation and Codingmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous research in multiparty conversations suggests that people most likely look at the person who is speaking or whom they are speaking to (Vertegaal, Slagter, van der Veer, & Nijholt, 2000). In addition, Hirvenkari et al (2013) reported that after a turn transition the gaze is directed towards the speaking person. Therefore it could be assumed that non-involved observers are also inclined to look at the speaker, while following the dyadic conversation.…”
Section: Introductionmentioning
confidence: 99%